Design and development of innovative ceiling fan cleaner - Farzana, Dusuki (2019)
Most of South East Asia especially in Malaysia, ceiling fans will be installed even though some houses use air conditioning as their cooling system. Ceiling fans create a tremendous amount of air flow, and dust is thrown around the room. The air always has a great deal of dust in it where larger particles can see, and microscopic. Large volume of the circulating air hits and collects dust on the blades of the fan. The traditional ways of cleaning the ceiling fan required users use a wet cloth and get up to the height of ceiling fan using a step ladder or use an extension rod with a brush. However, these methods are dangerous because a user may fall down from the ladder and cause environment hygiene problem. Furthermore, a user need to take more time to finish clean all the fan blades by using a non-suitable material which most of the dust will falls down to the floor during cleaning activities. Therefore, a portable ceiling fan cleaner are developed for the ease of operation in cleaning ceiling fan blades. The extension hose of vacuum cleaner can be attached to the ceiling fan cleaner to suck the dust and grimes from the blades without use a step ladder or stool. This design also can reduce time consumption in cleaning ceiling fan blade which took less than four (4) minutes. Next, a fan is used for thermal comfort which create a wind chill and give lower temperatures directly. By using the best material, all types of dust can be removed in a matter of minutes hence create high velocity of wind speed of fan blades and feeling cold which gives a good comfort for human daily activities.